2019
DOI: 10.3390/f10121153
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Translocation of Phosphorus, Calcium, Magnesium, and Aluminum in Pinus massoniana Lamb. Seedlings Inoculated with Laccaria bicolor Growing in an Acidic Yellow Soil

Abstract: Research Highlights: We demonstrate that ectomycorrhizal (ECM) fungi improve plant aluminum (Al)-tolerance in the field and Laccaria bicolor S238A is a promising ECM isolate. Furthermore, we interpret the underlying nutritional mechanism that ECM inoculation facilitates aboveground biomass production as well as nutrients accumulation and translocation. Background and Objectives: Al toxicity is a primary limiting factor for plants growing in acidic soils. Hydroponic/sand culture studies have shown that some ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In addition, Lactarius deliciosus and Suillus luteus cultured in vitro on Pachlewski liquid medium could reduce active Al 3ϩ concentrations while increasing P availability in response to Al stress (24). Compared with their non-ECM-inoculated counterparts, both biomass production and P uptake were significantly higher in L. bicolor-inoculated P. massoniana grown in acid yellow soil (25) and Pisolithus tinctorius-inoculated Pinus densiflora cultured on perlite containing Al 3ϩ (26). In a neutral purple soil (pH 6.8), Al-bound P (Al-P) and Ca-bound P (Ca-P) decreased significantly when the soil was incubated in vitro with Boletus sp.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…In addition, Lactarius deliciosus and Suillus luteus cultured in vitro on Pachlewski liquid medium could reduce active Al 3ϩ concentrations while increasing P availability in response to Al stress (24). Compared with their non-ECM-inoculated counterparts, both biomass production and P uptake were significantly higher in L. bicolor-inoculated P. massoniana grown in acid yellow soil (25) and Pisolithus tinctorius-inoculated Pinus densiflora cultured on perlite containing Al 3ϩ (26). In a neutral purple soil (pH 6.8), Al-bound P (Al-P) and Ca-bound P (Ca-P) decreased significantly when the soil was incubated in vitro with Boletus sp.…”
mentioning
confidence: 78%
“…Growth inhibition is an index used extensively for the assessment of Al toxicity (5,36). Numerous studies have demonstrated that various ECM fungi, including L. bicolor (25), P. tinctorius (26,31,37), and P. involutus (38), could enhance plant growth and Al tolerance in acidic culture media. P. tinctorius inoculation also enhanced P. strobus shoot but not root growth with ϩAl treatment (31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations